The Urgency of Identification of Extended Spectrum Beta-Lactamase (ESBL) Produced Bacteria in Indonesia - Rida Tiffarent; Conny Riana Tjampakasari; Fathia Ramadhani; Herjuno Ari Nugroho; Syaiful Rizal; Nina Herlina; Nova Dilla Yanthi; Sugiyono Saputra (WARTAZOA. Indonesian Bulletin of Animal and Veterinary Sciences, 2022)
The Extended Spectrum Beta-Lactamase (ESBL) produced bacterias are the bacteria group that have resistant characteristic to beta-lactam antibiotics because of their ability to hydrolyze these antibiotics. This is a global health issue because they can reduce the treatment effectiveness and endanger human health. The ESBL produced bacterias were reported that they can be isolated from samples originated from animals, humans, and environment, indicating the potency of the resistant genes spreading widely. Therefore, it is necessary to take the preventive and control measures across sectors and stakeholders to limit the widespread transmission of resistant genes carried-bacteria, so the ESBL produced bacteria prevalence can be monitored. This article aims to present the studies of ESBL produced bacteria in Indonesia and the comparison with another country based on published journals and data. Even though these bacterias were identified in various samples, the reports from animals (wild and domestic) and the environment are still available in small numbers in Indonesia. The comprehensive studies from various fields (one health spectrum) in detection and surveillance are needed to support the awareness of antimicrobial resistance. Surveillance can be conducted thorough microbial approach such as culture and identification, and molecular methods. The surveillance data can be used as the source for planning and controlling program of antimicrobial resistance especially ESBL produced bacterias in Indonesia.